Особливості вчинення правочинів з переданим у довірчу власність майном: аналіз цивільного законодавства України - Некіт, Катерина Георгіївна; Некит, Екатерина Георгиевна; Nekit, Ekaterina G. (My University, 2014)
Статтю присвячено дослідженню особливостей вчинення правочинів з переданим у довірчу власність майном. Визначено, що право вчиняти правочини з майном, переданим у довірчу власність, має лише довірчий власник. Установник довірчої власності на період існування довірчої власності втрачає можливість вчинення будь-яких правочинів щодо переданого в довірчу власність майна.

Статья посвящена исследованию особенностей закпючения сделок с переданним в доверительную собственность имуществом. Определено, что право совершать сделки с имуществом, переданним в доверительную собственность, имеет только доверительный собственник. Учредитель доверительной собственности на период существования доверительной собственности теряет возможность совершения каких-либо сделок относительно переданного в доверительную собственность имущества.

The article is devoted to research of features of the conclusion of transactions with the trust property. It is defined that the right to conclude transactions with the trust property only the trustee has. The trustor loses possibility of conclusion of any transactions with the trust property. The subject of any relations concerning this property is the trustee, who thus acts in interests of the founder of trust property or the beneficiary, but at sole discretion acts. Thus obligations which arise when transactions are concluded by the trustee, are satisfied, first of all, at the expense of the estate which is object of trust property, and on condition of its insufficiency the founder of trust property musts answer with other his property. At the solution of the question of features of transactions with the trust property definition of the moment from which the trustee has the right to make transactions with this property is important. Today the contract of trust property is considered concluded from the moment of the notarial certificate, however, the rights of the trustee arise only after their state registration. Respectively, until the state registration of the right of trust the trustee has no right to make any transactions with the trust property. From the moment of the state registration of the right of of trust there is also a duty of the founder of trust property not to interfere with activity of the of trustee. Therefore, from this point the founder of of trust property loses the right forthe conclusion oftransactions with the oftrust property.
Некіт К. Г. Особливості вчинення правочинів з переданим у довірчу власність майном: аналіз цивільного законодавства України / К. Г. Некіт // Юридичний науковий електронний журнал. - 2014. - № 5. - С. 33-35.
Keywords: довірча власність; установник; власник; правочин; майно; доверительная собственность; учредитель; собственник; сделка; имущество; trust property; trustor; owner; transaction; property